2023
DOI: 10.3390/biomedicines11030895
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Dynamics and Neurobiology of Non-Response to Antipsychotics, Relevance for Treatment Resistant Schizophrenia: A Systematic Review and Critical Appraisal

Abstract: Treatment resistant schizophrenia (TRS) is characterized by a lack of, or suboptimal response to, antipsychotic agents. The biological underpinnings of this clinical condition are still scarcely understood. Since all antipsychotics block dopamine D2 receptors (D2R), dopamine-related mechanisms should be considered the main candidates in the neurobiology of antipsychotic non-response, although other neurotransmitter systems play a role. The aims of this review are: (i) to recapitulate and critically appraise th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 246 publications
0
2
0
Order By: Relevance
“…Surprisingly, longitudinal studies looking at the overall SCZ recovery rate during the 20th century found little change since 1900, and, according to some studies, a steadily deteriorating outcome [99][100][101]. Moreover, contrary to the expectations of most researchers and clinicians, the proportion of patients with "good" outcomes has not increased in the decades following the discovery of antipsychotic drugs [7,90,102,103]. For example, a large meta-analysis of 114 follow-up studies by Warner R. looked at the time period from 1900 to 1996 and found the following rates of complete recovery and employment [101] These data led the author to conclude that "recovery rates for patients admitted following the introduction of the antipsychotic drugs are no better than for those admitted after the Second World War or during the first two decades of the twentieth century" (page 78).…”
Section: Dh and Scz Outcome Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, longitudinal studies looking at the overall SCZ recovery rate during the 20th century found little change since 1900, and, according to some studies, a steadily deteriorating outcome [99][100][101]. Moreover, contrary to the expectations of most researchers and clinicians, the proportion of patients with "good" outcomes has not increased in the decades following the discovery of antipsychotic drugs [7,90,102,103]. For example, a large meta-analysis of 114 follow-up studies by Warner R. looked at the time period from 1900 to 1996 and found the following rates of complete recovery and employment [101] These data led the author to conclude that "recovery rates for patients admitted following the introduction of the antipsychotic drugs are no better than for those admitted after the Second World War or during the first two decades of the twentieth century" (page 78).…”
Section: Dh and Scz Outcome Studiesmentioning
confidence: 99%
“…This model was further substantiated by the 1970s observation that amphetamine enhanced dopaminergic signaling, often exacerbating psychotic symptoms [4]. However, the realization that antipsychotic drugs exert properties, seemingly unrelated to DA, such as antimicrobial, antiviral, antiproliferative, cell cycle arrest, autophagy activation, alteration of iron metabolism, DNA methylation, and telomere elongation, led to the third DH revision, which emphasized genetic and epigenetic input in dopaminergic transmission [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, neurochemical attempts to characterize the molecular basis of the disorder have also been conducted, and the alteration of the dopaminergic brain networks have been encountered [10,11]. SZ seems to also be associated with states of increased inflammation and oxidative stress, as well as with alterations of the innate immunity [12].…”
Section: Introductionmentioning
confidence: 99%
“…The long D2R isoform, predominantly expressed postsynaptically in striatal medium spiny neurons, acts as an auto-or hetero-receptor and induces motor activity upon activation by DA or agonists (Dal Toso et al, 1989;David et al, 1991;Usiello et al, 2000;Ford, 2014;Shioda, 2017;Radl et al, 2018;Quintana and Beaulieu, 2019). Both D2R isoforms play key roles in the DAergic system and do not function properly in schizophrenia (Oda et al, 2015;Shioda, 2017;Zhou et al, 2022;Iasevoli et al, 2023). The DAergic system regulates locomotion (Beninger, 1983;Groenewegen, 2003), motivational aspects of behavior like exploration, novelty and reward seeking (Menegas et al, 2017) as well as anxiety (Steiner et al, 1997;Brañdao and Coimbra, 2019;Juza et al, 2023).…”
Section: Introductionmentioning
confidence: 99%